Nylon-polyolefin polymer alloy material and preparation method thereof

CN122668536BActive Publication Date: 2026-10-27JIANGSU JINGLIHUA NEW MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611131038.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-29
Publication Date
2026-10-27
Estimated Expiration
2046-07-29

AI Technical Summary

Technical Problem

但是,尼龙树脂分子链极性较强,聚烯烃树脂分子链极性较低,两者直接熔融共混时相容性较差,容易出现分散相尺寸不稳定、界面结合不足和相间应力传递不充分的问题

Benefits of technology

[0032]与现有技术相比,本发明的有益效果为:本发明通过分别构建长链尼龙-聚烯烃界面母粒和尼龙6-聚烯烃界面母粒,使不同尼龙链段分别通过马来酸酐基团和环氧基团连接至聚烯烃链段,避免单一相容剂在熔融共混过程中随机反应导致界面连接结构不稳定的问题。长链尼龙低聚物能够在聚烯烃相与尼龙相之间形成过渡链段,尼龙6低聚物能够与尼龙基体保持链段相容,并为后段双噁唑啉反应提供羧基位点。双噁唑啉类化合物在下游加入后参与尼龙相及界面区域的端基反应,减少前段反应中的无序消耗。由此得到的尼龙-聚烯烃高分子合金材料在湿热循环或吸湿使用环境下能够维持较稳定的界面结合状态,降低因两相尺寸响应差异引起的界面衰减,改善制品翘曲控制和缺口冲击性能保持。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122668536B_ABST
    Figure CN122668536B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of polymer alloy materials, and provides a nylon-polyolefin polymer alloy material and a preparation method thereof.The preparation method first prepares amino-terminated long-chain nylon oligomer and carboxyl-terminated nylon 6 oligomer, and then respectively carries out melt reaction with maleic anhydride grafted polyolefin and epoxy group-containing polyolefin to obtain long-chain nylon-polyolefin interface master batch and nylon 6-polyolefin interface master batch; subsequently, the two kinds of interface master batches are melt-mixed with nylon resin, polyolefin resin, antioxidant and lubricant, and a bisoxazoline compound is added downstream, and the nylon-polyolefin polymer alloy material is obtained through extrusion, cooling and granulation. The application constructs polyolefin interface master batches with different nylon segments in parallel, so that the interface region has a segment connection structure compatible with the nylon phase and the polyolefin phase, which can reduce the interface attenuation after hygrothermal cycling, and improve the interface retention state, dimensional stability and notched impact performance retention of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymer alloy materials technology, and relates to a nylon-polyolefin polymer alloy material and its preparation method. Background Technology

[0002] Nylon materials possess good mechanical strength, wear resistance, oil resistance, and processing performance, and are commonly used in automotive parts, electrical and electronic components, and engineering structural parts. Polyolefin materials are characterized by low water absorption, low density, and good chemical resistance. High-molecular alloying of nylon resin and polyolefin resin is a common method to improve the hygroscopic dimensional changes of nylon materials, adjust toughness, and reduce material costs. However, nylon resin molecules have strong polarity, while polyolefin resin molecules have low polarity, resulting in poor compatibility when directly melt-blended. This can easily lead to problems such as unstable dispersed phase size, insufficient interfacial bonding, and inadequate interphase stress transfer. Existing technologies typically use maleic anhydride-grafted polyolefins, epoxy-containing polyolefins, or other reactive compatibilizers to improve the bonding between the nylon and polyolefin phases. However, most methods still rely on single-stage blending with a single compatibilizer, resulting in randomly distributed reaction sites in the molten system and a relatively simple interfacial bonding structure.

[0003] Existing nylon-polyolefin polymer alloy materials exhibit inconsistent dimensional responses between the nylon and polyolefin phases under humid heat cycling or moisture-absorbing conditions. Furthermore, the interfacial bonding structure formed by conventional compatibilizers is difficult to maintain interfacial stability, leading to a decay of the interfacial bonding state after humid heat. This, in turn, increases product warpage, exacerbates molding shrinkage differences, and reduces the retention rate of notched impact resistance. Summary of the Invention

[0004] To address the shortcomings of existing technologies, the present invention aims to provide a nylon-polyolefin polymer alloy material and its preparation method. First, amino-terminated long-chain nylon oligomers and carboxyl-terminated nylon 6 oligomers are prepared, and then reacted with maleic anhydride-grafted polyolefins and epoxy-containing polyolefins to obtain two interface masterbatches. These masterbatches are then melt-mixed with nylon resin and polyolefin resin, and a bisoxazoline compound is added downstream to obtain the nylon-polyolefin polymer alloy material, thereby meeting the needs of actual production.

[0005] To achieve this objective, the present invention adopts the following technical solution: In a first aspect, the present invention provides a method for preparing a nylon-polyolefin polymer alloy material, the method comprising the following steps: S1, long-chain nylon chain-forming raw materials are subjected to polycondensation reaction with diamine end-group regulators to obtain amino-terminated long-chain nylon oligomers; S2, caprolactam, 6-aminohexanoic acid and dicarboxylic acid regulators are subjected to ring-opening polymerization and polycondensation reaction to obtain carboxyl-terminated nylon 6 oligomers; S3, the amino-terminated long-chain nylon oligomer is subjected to a first melt reaction with maleic anhydride-grafted polyolefin to obtain long-chain nylon-polyolefin interface masterbatch. S4, the carboxyl-terminated nylon 6 oligomer is subjected to a second melt reaction with an epoxy-containing polyolefin to obtain nylon 6-polyolefin interface masterbatch; S5, Nylon resin, polyolefin resin, the long-chain nylon-polyolefin interface masterbatch, the nylon 6-polyolefin interface masterbatch, antioxidant and lubricant are added to the first feed port of the twin-screw extruder and melt-mixed in the first melt mixing section to obtain the first melt; S6, a bisoxazoline compound is added to a twin-screw extruder through a side feed port located downstream of the first melt mixing section, and melt-mixed with the first melt in the second melt mixing section. After extrusion, cooling, and pelletizing, a nylon-polyolefin polymer alloy material is obtained.

[0006] Preferably, in S1, the long-chain nylon chain-forming raw material and the diamine end-group regulator are used in any of the following combinations: Combination 1, wherein the long-chain nylon chain-forming raw material is 12-aminododecanoic acid, and the diamine end-group regulator is 1,12-dodecanediamine, to obtain amino-terminated nylon 12 oligomer; Combination 2, wherein the long-chain nylon chain-forming raw materials are hexamethylenediamine and sebacic acid, and the diamine end-group regulator is hexamethylenediamine, to obtain amino-terminated nylon 610 oligomer; Combination 3, the long-chain nylon chain-forming raw materials are decanediamine and sebacic acid, and the diamine end-group regulator is decanediamine, to obtain amino-terminated nylon 1010 oligomer.

[0007] Preferably, in S1, when the amino-terminated long-chain nylon oligomer is an amino-terminated nylon 12 oligomer, the mass ratio of 12-aminododecanoic acid to 1,12-dodecanediamine is 100:(2-10); when the amino-terminated long-chain nylon oligomer is an amino-terminated nylon 610 oligomer, the mass ratio of the total amount of hexamethylenediamine to sebacic acid is (59-66):100; when the amino-terminated long-chain nylon oligomer is an amino-terminated nylon 1010 oligomer, the mass ratio of the total amount of sebacic acid to sebacic acid is (88-98):100.

[0008] Preferably, in S2, the mass ratio of caprolactam, 6-aminohexanoic acid and dicarboxylic acid regulator is (80-95):(5-20):(2-8), and the dicarboxylic acid regulator is one or both of adipic acid and sebacic acid.

[0009] Preferably, the number average molecular weight of the amino-terminated long-chain nylon oligomer is 1900-2800 g / mol, and the amino end group concentration is 360-840 mmol / kg; the number average molecular weight of the carboxyl-terminated nylon 6 oligomer is 900-2300 g / mol, and the carboxyl end group concentration is 460-1180 mmol / kg, and the molar ratio of the carboxyl end group concentration to the amino end group concentration is (0.8-1.4):1.

[0010] Preferably, in S1, the polycondensation reaction includes pre-polycondensation and melt polycondensation, wherein the pre-polycondensation temperature is 180-200℃ and the time is 1.5-3h; and the melt polycondensation temperature is 220-245℃ and the time is 2-4h.

[0011] Preferably, in S2, the ring-opening polymerization temperature is 180-200℃ and the time is 2-4h; the condensation polymerization temperature is 230-250℃ and the time is 2-4h.

[0012] Preferably, S1 and S2 are carried out under a nitrogen atmosphere, and sodium hypophosphite is added to S1 and S2, wherein the mass ratio of sodium hypophosphite to the total amount of reaction raw materials is (0.01-0.1):100.

[0013] Preferably, in S3, the mass ratio of the amino-terminated long-chain nylon oligomer to the maleic anhydride-grafted polyolefin is (5-25):(75-95), the temperature of the first melting reaction is 190-230℃, and the reaction time is 1-5 min.

[0014] Preferably, in S4, the mass ratio of the carboxyl-terminated nylon 6 oligomer to the epoxy-containing polyolefin is (5-30):(70-95), the temperature of the second melting reaction is 200-240℃, and the reaction time is 1-5 min.

[0015] Preferably, the molar ratio of the epoxy group in the epoxy-containing polyolefin to the carboxyl end group in the carboxyl-terminated nylon 6 oligomer is (0.2-0.8):1.

[0016] Preferably, the maleic anhydride-grafted polyolefin is one or both of maleic anhydride-grafted ethylene-octene copolymer and maleic anhydride-grafted polypropylene; the melt flow rate of the maleic anhydride-grafted ethylene-octene copolymer at 190°C and 2.16 kg is 0.5-10 g / 10 min, and the melt flow rate of the maleic anhydride-grafted polypropylene at 230°C and 2.16 kg is 5-50 g / 10 min.

[0017] Preferably, the epoxy-containing polyolefin is one or both of ethylene-glycidyl methacrylate copolymer and ethylene-acrylate-glycidyl methacrylate copolymer, and the mass content of glycidyl methacrylate structural units in the epoxy-containing polyolefin is 2-10 wt.%.

[0018] Preferably, in S5 and S6, the mass ratio of the nylon resin, polyolefin resin, long-chain nylon-polyolefin interface masterbatch, nylon 6-polyolefin interface masterbatch, antioxidant, lubricant and bisoxazoline compound is (50-75):(10-30):(3-12):(3-12):(0.2-1.5):(0.2-1.5):(0.2-1.2).

[0019] Preferably, the nylon resin is one or both of nylon 6 and nylon 66; the polyolefin resin is one or both of polypropylene and ethylene-octene copolymer; and the bisoxazoline compound is one or both of 2,2′-(1,3-phenylene)dioxazoline and 2,2′-(1,4-phenylene)dioxazoline.

[0020] Preferably, in step S5, MXD6 (poly(m-phenylene adipamide)) is also added, wherein the mass ratio of MXD6 to nylon resin is (3-12):(50-75).

[0021] Preferably, the antioxidant is one or two of hindered phenolic antioxidants and phosphite antioxidants; the lubricant is one or more of ethylene bis-stearamide, pentaerythritol stearate, and calcium stearate.

[0022] Preferably, the twin-screw extruder is a co-rotating twin-screw extruder with a length-to-diameter ratio of 44-52 and a screw speed of 250-500 r / min; the temperature of the first melt mixing section is 240-275℃, and the temperature of the second melt mixing section is 240-270℃; the nylon resin and MXD6 are dried before being added to the twin-screw extruder, and the drying temperature is 100-120℃ for 6-10 hours.

[0023] Long-chain nylon raw materials undergo polycondensation in the presence of diamine end-group regulators, where carboxyl and amino groups dehydrate to form amide bonds. When the diamine component is in excess relative to the carboxyl component, the polycondensation product retains amino end groups, forming amino-terminated long-chain nylon oligomers. These oligomers contain polyamide segments and terminal amino groups. The polyamide segments can form chain entanglement and hydrogen bonding with the nylon phase, while the terminal amino groups can participate in subsequent acid anhydride reactions.

[0024] Caprolactam undergoes ring-opening under the influence of the carboxyl group of 6-aminohexanoic acid, generating nylon 6 segments containing both amino and carboxyl groups. Dicarboxylic acid regulators participate in the polycondensation equilibrium, increasing the proportion of carboxyl end groups in the oligomer chains. The resulting carboxyl-terminated nylon 6 oligomers are not single molecular structures, but rather a collection of oligomers with a statistically distributed distribution of end groups, where the carboxyl end groups provide reaction sites for subsequent epoxy ring-opening and bisoxazoline ring-opening reactions.

[0025] When amino-terminated long-chain nylon oligomers are melt-mixed with maleic anhydride-grafted polyolefins, the terminal amino groups of the oligomers attack the carbonyl carbon in the maleic anhydride ring, causing ring-opening and generating an amide acid structure. Under melt shearing and devolatilization conditions, the amide acid structure can be further dehydrated to form an imide structure, or it can remain as an amide acid on the polyolefin graft chain. This reaction allows the long-chain nylon oligomers to attach to polyolefin segments through anhydride grafting sites, forming a long-chain nylon-polyolefin interfacial masterbatch. The polyolefin backbone is compatible with the polyolefin resin, and the grafted long-chain nylon segments can enter the adjacent region of the nylon phase, thereby forming a connected structure containing polyolefin and polyamide segments at the interface between the two phases.

[0026] When carboxyl-terminated nylon 6 oligomers are melt-mixed with epoxy-containing polyolefins, the carboxylic acid protons in the carboxyl terminus activate the epoxy group, and the carboxylic acid group undergoes nucleophilic attack on the epoxy ring, leading to ring-opening and the formation of a β-hydroxy ester linker. This reaction allows the nylon 6 oligomer to attach to the epoxy-containing polyolefin segment via the carboxyl terminus, forming a nylon 6-polyolefin interfacial masterbatch. By controlling the stoichiometric relationship between the epoxy and carboxyl terminus groups, the epoxy groups consume some of the carboxyl terminus groups, while the carboxyl terminus groups that do not participate in the epoxy ring-opening remain in the nylon 6 oligomer segment, becoming reaction sites for subsequent bisoxazoline reactions.

[0027] When the two types of interface masterbatches are melt-mixed with nylon resin and polyolefin resin, the polyolefin segments in the interface masterbatches enter the polyolefin phase, while the nylon oligomer segments enter the nylon phase or remain in the vicinity of the nylon phase. Melt shearing disperses the polyolefin phase into droplets or continuous phase fragments, and the interface masterbatches are distributed at the interface between the two phases, reducing the interfacial tension between the two phases and limiting the co-polymerization of the dispersed phases. Long-chain nylon segments connect to the polyolefin side phase, while nylon 6 segments are compatible with the nylon matrix. The two types of interface masterbatches provide interfacial bonding units with different segment lengths and end-group states, so that the interfacial region no longer relies solely on maleic anhydride-grafted polyolefins for bonding.

[0028] When the bisoxazoline compound is added through the downstream feed port, the nylon resin and two interface masterbatches have already completed melt dispersion. The bisoxazoline enters the melt environment dominated by the nylon phase and the interface region. The oxazoline ring undergoes a ring-opening reaction with the carboxyl end group to generate an amide ester type linkage structure. The reaction targets include the terminal carboxyl groups of the nylon resin, the carboxyl end groups retained in the nylon 6-polyolefin interface masterbatch, and a small number of carboxyl sites generated during the melting process. The bifunctional structure of the bisoxazoline can form molecular links between the two carboxyl sites, causing chain extension or bridging of some nylon segments and interface masterbatch segments.

[0029] The downstream addition of bisoxazoline bypasses the anhydride and epoxy reaction stages in the upstream masterbatch preparation, reducing its premature consumption by carboxyl end groups before the formation of the interfacial masterbatch. The residence time and shearing action in the second melt mixing stage ensure that bisoxazoline primarily participates in the reaction within the already formed nylon phase and interfacial region, rather than reacting randomly with oligomers during the initial feeding stage. Thus, maleic anhydride-grafted polyolefins correspond to amino-terminated long-chain nylon oligomers, epoxy-containing polyolefins correspond to carboxyl-terminated nylon 6 oligomers, and bisoxazoline corresponds to residual carboxyl end groups and nylon resin end carboxyl groups. Each reaction site is consumed in stages during processing, reducing competitive reactions between different functional groups.

[0030] During cooling, the nylon phase crystallizes, while the polyolefin phase crystallizes or solidifies and disperses. Polyolefin segments in the interfacial masterbatch move with the polyolefin phase, while polyamide oligomer segments move with the crystallization of the nylon phase and the amorphous regions. Grafted segments at the interface play a role in stress transfer during the cooling and shrinkage of the two phases. Under humid and hot conditions, after the nylon phase absorbs water, the hydrogen bonds between its segments are partially competed for by water molecules, increasing the mobility of the amorphous segments. The polyolefin phase absorbs less water, resulting in a lower dimensional response than the nylon phase. The long-chain nylon-polyolefin masterbatch and nylon 6-polyolefin masterbatch at the interface provide segmental connections across the two phases. The amide ester-type connection structure formed by bisoxazoline restricts the migration of some end-group segments, making it difficult for the interface to withstand the shear forces caused by the difference in hygroscopic expansion of the nylon phase and the dimensional response of the polyolefin phase solely through physical contact.

[0031] In a second aspect, the present invention provides a nylon-polyolefin polymer alloy material prepared by the preparation method described in the first aspect.

[0032] Compared with existing technologies, the beneficial effects of this invention are as follows: By separately constructing long-chain nylon-polyolefin interface masterbatches and nylon 6-polyolefin interface masterbatches, different nylon segments are connected to polyolefin segments via maleic anhydride groups and epoxy groups, respectively, avoiding the problem of unstable interfacial bonding structures caused by random reactions of a single compatibilizer during melt blending. Long-chain nylon oligomers can form transition segments between the polyolefin and nylon phases, while nylon 6 oligomers can maintain segment compatibility with the nylon matrix and provide carboxyl sites for the subsequent bisoxazoline reaction. The bisoxazoline compounds, added downstream, participate in the end-group reactions of the nylon phase and interfacial region, reducing disordered consumption in the preceding reactions. The resulting nylon-polyolefin polymer alloy material can maintain a relatively stable interfacial bonding state under humid heat cycling or hygroscopic use environments, reducing interfacial attenuation caused by differences in the size response of the two phases, and improving product warpage control and notched impact resistance. Attached Figure Description

[0033] Figure 1 This is a schematic diagram of the structure of the amino-terminated long-chain nylon oligomer provided by the present invention; Figure 2 This is a schematic diagram of the structure of the carboxyl-terminated nylon 6 oligomer provided by the present invention. Detailed Implementation

[0034] The technical solutions of the present invention will be described in detail below with reference to specific embodiments and accompanying drawings. The embodiments described herein are specific implementations of the present invention, used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary, and should not be construed as limiting the implementation methods or the scope of protection of the present invention. In addition to the embodiments described herein, those skilled in the art can employ other obvious technical solutions based on the content disclosed in the claims and specification of this application. These technical solutions include those that make any obvious substitutions and modifications to the embodiments described herein.

[0035] The chemical reagents used in the embodiments and comparative examples of this invention are all commercially available products and have not undergone any further purification treatment.

[0036] The concentration of terminal groups was determined by acid-base titration. Before testing, the oligomer samples were dried to constant weight in a vacuum drying oven. For amino terminal group concentration testing, the dried sample was dissolved in a phenol-methanol mixed solvent, titrated with hydrochloric acid-methanol standard solution using bromophenol blue as an indicator, and a blank test was performed simultaneously. For carboxyl terminal group concentration testing, the dried sample was dissolved in benzyl alcohol, titrated with potassium hydroxide-benzyl alcohol standard solution using phenolphthalein as an indicator, and a blank test was performed simultaneously. The terminal group concentration was calculated as C = (V - V0) × c × 1000 / m, where C is the terminal group concentration in mmol / kg; V is the volume of standard solution consumed in the sample titration in mL; V0 is the volume of standard solution consumed in the blank titration in mL; c is the concentration of the standard solution in mol / L; and m is the sample mass in g.

[0037] The molar ratio of carboxyl terminus concentration to amino terminus concentration is obtained by dividing the measured carboxyl terminus concentration by the amino terminus concentration.

[0038] Number-average molecular weight was determined by gel permeation chromatography. Before testing, the oligomer samples were dried to constant weight in a vacuum drying oven, and the dried samples were weighed and dissolved in hexafluoroisopropanol. For samples with insufficient dissolution, sodium trifluoroacetate was added to the hexafluoroisopropanol before dissolution. The sample solution was filtered through a microporous membrane and then injected for testing. Hexafluoroisopropanol was used as the mobile phase, and polymethyl methacrylate (PMMA) standard samples were used for calibration. The number-average molecular weight of the oligomers was calculated based on the gel permeation chromatography results.

[0039] In this invention, the amino-terminated long-chain nylon oligomer is a long-chain nylon oligomer with amino-terminal groups, and its structure is shown in the figure below. Figure 1 As shown; where R1 and R2 represent hydrocarbon segments in long-chain nylon oligomers, and n represents the number of repeating units in the oligomer segment. Carboxyl-terminated nylon 6 oligomers are nylon 6 oligomers with carboxyl-terminated groups, and their structural diagram is shown below. Figure 2 As shown; where R represents the hydrocarbon segment introduced by the dicarboxylic acid regulator, and n represents the number of repeating units in the nylon 6 oligomer segment.

[0040] ethylene-octene copolymer using ENGAGE TM 8150 has a melt flow rate of 0.50 g / 10 min and a density of 0.868 g / cm³ at 190 °C and 2.16 kg. 3 Maleic anhydride-grafted ethylene-octene copolymer uses FUSABOND TM N493 has a melt flow rate of 1.6 g / 10 min and a density of 0.870 g / cm³ at 190 °C and 2.16 kg. 3The polypropylene used is PP1364E2 polypropylene homopolymer, which has a melt flow rate of 12 g / 10 min and a density of 0.900 g / cm³ at 230℃ and 2.16 kg. 3 The maleic anhydride-grafted polypropylene uses Polybond® 3150, which has a melt flow rate of 50 g / 10 min at 230°C and 2.16 kg, and a maleic anhydride content of 0.5 wt.%; the hindered phenolic antioxidant is specifically antioxidant 1010, and the phosphite antioxidant is specifically antioxidant 168.

[0041] Example 1 This embodiment provides a nylon-polyolefin polymer alloy material and its preparation method, the preparation method specifically including the following steps: S1, 12-aminododecanoic acid, 1,12-dodecanediamine, and sodium hypophosphite are added to a reaction vessel. The mass ratio of 12-aminododecanoic acid to 1,12-dodecanediamine is 100:2, and the mass ratio of sodium hypophosphite to the total mass of 12-aminododecanoic acid and 1,12-dodecanediamine is 0.04:100. After purging with nitrogen, the mixture is heated to 190°C for pre-polymerization for 2 hours, and then heated to 235°C for melt polymerization for 3 hours to obtain amino-terminated nylon 12 oligomers. The number average molecular weight of the amino-terminated nylon 12 oligomers is 2800 g / mol, and the amino end group concentration is 360 mmol / kg. S2, caprolactam, 6-aminohexanoic acid, adipic acid, and sodium hypophosphite were added to a reaction vessel. The mass ratio of caprolactam, 6-aminohexanoic acid, and adipic acid was 95:5:2, and the mass ratio of sodium hypophosphite to the total mass of caprolactam, 6-aminohexanoic acid, and adipic acid was 0.05:100. After purging with nitrogen, the mixture was heated to 190°C for ring-opening polymerization for 2.5 h, and then heated to 240°C for polycondensation for 3 h to obtain carboxyl-terminated nylon 6 oligomers. The number average molecular weight of the carboxyl-terminated nylon 6 oligomers was 2300 g / mol, the carboxyl-terminal concentration was 460 mmol / kg, and the molar ratio of carboxyl-terminal concentration to amino-terminal concentration was 1.3:1. S3, amino-terminated nylon 12 oligomer and maleic anhydride-grafted ethylene-octene copolymer are added to a twin-screw extruder at a mass ratio of 5:95 and subjected to a first melt reaction at 220°C for 3 minutes to obtain long-chain nylon-polyolefin interface masterbatch; the melt flow rate of the maleic anhydride-grafted ethylene-octene copolymer is 2 g / 10 min at 190°C and 2.16 kg. S4, the carboxyl-terminated nylon 6 oligomer and ethylene-glycidyl methacrylate copolymer are added to a twin-screw extruder at a mass ratio of 30:70, and a second melt reaction is carried out at 215°C for 4 minutes to obtain nylon 6-polyolefin interface masterbatch; the mass content of glycidyl methacrylate structural units in the ethylene-glycidyl methacrylate copolymer is 2 wt.%, and the molar ratio of epoxy groups to carboxyl-terminated nylon 6 oligomers is 0.2:1; S5, Nylon 6, ethylene-octene copolymer, long-chain nylon-polyolefin interface masterbatch, nylon 6-polyolefin interface masterbatch, hindered phenolic antioxidant, and ethylene bis-stearamide are added to the first feed port of a co-rotating twin-screw extruder and melt-mixed in the first melt mixing section to obtain the first melt; the mass ratio of nylon 6, ethylene-octene copolymer, long-chain nylon-polyolefin interface masterbatch, nylon 6-polyolefin interface masterbatch, hindered phenolic antioxidant, ethylene bis-stearamide, and 2,2′-(1,3-phenylene)dioxazoline is 50:20:3:10:0.8:0.6:0.2; S6, 2,2′-(1,3-phenylene)dioxazoline is added to a co-rotating twin-screw extruder through a side feed port located downstream of the first melt mixing section. It is melt-mixed with the first melt in the second melt mixing section. After extrusion, cooling, and pelletizing, nylon-polyolefin polymer alloy material is obtained. The co-rotating twin-screw extruder has an aspect ratio of 48, a screw speed of 350 r / min, a first melt mixing section temperature of 255℃ for 1.2 min, and a second melt mixing section temperature of 265℃ for 0.7 min. Nylon 6 is dried at 100℃ for 6 h before being added to the co-rotating twin-screw extruder.

[0042] Example 2 This embodiment provides a nylon-polyolefin polymer alloy material and its preparation method, the preparation method specifically including the following steps: S1, hexamethylenediamine, sebacic acid, and sodium hypophosphite are added to a reaction vessel. The mass ratio of hexamethylenediamine to sebacic acid is 66:100, and the mass ratio of sodium hypophosphite to the total mass of hexamethylenediamine and sebacic acid is 0.1:100. After purging with nitrogen, the mixture is heated to 180°C for pre-polymerization for 3 hours, and then heated to 245°C for melt polymerization for 3 hours to obtain amino-terminated nylon 610 oligomer. The number average molecular weight of the amino-terminated nylon 610 oligomer is 2400 g / mol, and the amino end group concentration is 840 mmol / kg. S2, caprolactam, 6-aminohexanoic acid, sebacic acid, and sodium hypophosphite were added to a reaction vessel. The mass ratio of caprolactam, 6-aminohexanoic acid, and sebacic acid was 80:20:8, and the mass ratio of sodium hypophosphite to the total mass of caprolactam, 6-aminohexanoic acid, and sebacic acid was 0.01:100. After purging with nitrogen, the mixture was heated to 180°C for ring-opening polymerization for 4 hours, and then heated to 250°C for polycondensation for 2 hours to obtain carboxyl-terminated nylon 6 oligomers. The number average molecular weight of the carboxyl-terminated nylon 6 oligomers was 900 g / mol, the carboxyl-terminated group concentration was 1180 mmol / kg, and the molar ratio of carboxyl-terminated group concentration to amino-terminated group concentration was 1.4:1. S3, amino-terminated nylon 610 oligomer and maleic anhydride-grafted polypropylene are added to a twin-screw extruder at a mass ratio of 25:75 and subjected to a first melt reaction at 230°C for 1 min to obtain long-chain nylon-polyolefin interface masterbatch; the melt flow rate of the maleic anhydride-grafted polypropylene at 230°C and 2.16 kg is 50 g / 10 min. S4, the carboxyl-terminated nylon 6 oligomer and the ethylene-acrylate-glycidyl methacrylate copolymer are added to a twin-screw extruder at a mass ratio of 5:95, and a second melt reaction is carried out at 200°C for 5 minutes to obtain nylon 6-polyolefin interface masterbatch; the mass content of glycidyl methacrylate structural units in the ethylene-acrylate-glycidyl methacrylate copolymer is 10 wt.%, and the molar ratio of epoxy groups to carboxyl-terminated nylon 6 oligomers is 0.8:1; S5, Nylon 66, polypropylene, long-chain nylon-polyolefin interface masterbatch, nylon 6-polyolefin interface masterbatch, MXD6, hindered phenolic antioxidant, phosphite antioxidant, and pentaerythritol stearate are added to the first feed port of a co-rotating twin-screw extruder and melt-mixed in the first melt mixing section to obtain the first melt; the mass ratio of nylon 66, polypropylene, long-chain nylon-polyolefin interface masterbatch, nylon 6-polyolefin interface masterbatch, hindered phenolic antioxidant, pentaerythritol stearate, and 2,2′-(1,4-phenylene)dioxazoline is 75:10:12:3:1.5:0.2:1.2, and the mass ratio of MXD6 to nylon 66 is 12:75; the mass ratio of the hindered phenolic antioxidant to the phosphite antioxidant is 1:1; S6, 2,2′-(1,4-phenylene)dioxazoline is fed into a co-rotating twin-screw extruder through a side feed port located downstream of the first melt mixing section. It is then melt-mixed with the first melt in the second melt mixing section. After extrusion, cooling, and pelletizing, a nylon-polyolefin polymer alloy material is obtained. The co-rotating twin-screw extruder has an aspect ratio of 52, a screw speed of 250 r / min, a first melt mixing section temperature of 275℃ for 0.3 min, and a second melt mixing section temperature of 270℃ for 0.2 min. Nylon 66 is dried at 120℃ for 8 h before being added to the co-rotating twin-screw extruder, and MXD6 is dried at 120℃ for 6 h before being added to the co-rotating twin-screw extruder.

[0043] Example 3 This embodiment provides a nylon-polyolefin polymer alloy material and its preparation method, the preparation method specifically including the following steps: S1, decanediamine, sebacic acid, and sodium hypophosphite are added to a reaction vessel. The mass ratio of total decanediamine to sebacic acid is 93:100, and the mass ratio of sodium hypophosphite to the total mass of decanediamine and sebacic acid is 0.06:100. After purging with nitrogen, the mixture is heated to 195°C for pre-polymerization for 1.5 hours, and then heated to 225°C for melt polymerization for 4 hours to obtain amino-terminated nylon 1010 oligomer. The number average molecular weight of the amino-terminated nylon 1010 oligomer is 1900 g / mol, and the amino end group concentration is 680 mmol / kg. S2, caprolactam, 6-aminohexanoic acid, adipic acid, sebacic acid, and sodium hypophosphite were added to a reaction vessel. The mass ratio of caprolactam, 6-aminohexanoic acid, and dicarboxylic acid regulator was 88:12:5, the mass ratio of adipic acid to sebacic acid was 1:1, and the mass ratio of sodium hypophosphite to the total mass of caprolactam, 6-aminohexanoic acid, adipic acid, and sebacic acid was 0.08:100. After purging with nitrogen, the temperature was raised to 200℃ for ring-opening polymerization for 2 hours, and then raised to 230℃ for polycondensation reaction for 4 hours to obtain carboxyl-terminated nylon 6 oligomers. The number average molecular weight of the carboxyl-terminated nylon 6 oligomers was 1600 g / mol, the carboxyl-terminal concentration was 760 mmol / kg, and the molar ratio of carboxyl-terminal concentration to amino-terminal concentration was 1.1:1. S3, amino-terminated nylon 1010 oligomer and maleic anhydride-grafted ethylene-octene copolymer are added to a twin-screw extruder at a mass ratio of 14:86, and the first melt reaction is carried out at 190°C for 4 min to obtain long-chain nylon-polyolefin interface masterbatch; the melt flow rate of the maleic anhydride-grafted ethylene-octene copolymer at 190°C and 2.16 kg is 0.5 g / 10 min; S4, the carboxyl-terminated nylon 6 oligomer and ethylene-glycidyl methacrylate copolymer are added to a twin-screw extruder at a mass ratio of 18:82, and a second melt reaction is carried out at 225°C for 2 minutes to obtain nylon 6-polyolefin interface masterbatch; the mass content of glycidyl methacrylate structural units in the ethylene-glycidyl methacrylate copolymer is 5 wt.%, and the molar ratio of epoxy groups to carboxyl-terminated nylon 6 oligomers is 0.35:1; S5, Nylon 6, ethylene-octene copolymer, long-chain nylon-polyolefin interface masterbatch, nylon 6-polyolefin interface masterbatch, MXD6, phosphite antioxidants and calcium stearate are added to the first feed port of a co-rotating twin-screw extruder and melt-mixed in the first melt mixing section to obtain the first melt; the mass ratio of nylon 6, ethylene-octene copolymer, long-chain nylon-polyolefin interface masterbatch, nylon 6-polyolefin interface masterbatch, phosphite antioxidants, calcium stearate and 2,2′-(1,3-phenylene)dioxazoline is 65:25:8:6:1.0:1.2:0.6, and the mass ratio of MXD6 to nylon 6 is 6:65; S6, 2,2′-(1,3-phenylene)dioxazoline is fed into a co-rotating twin-screw extruder through a side feed port located downstream of the first melt mixing section. It is melt-mixed with the first melt in the second melt mixing section. After extrusion, cooling, and pelletizing, nylon-polyolefin polymer alloy material is obtained. The length-to-diameter ratio of the co-rotating twin-screw extruder is 44, the screw speed is 420 r / min, the temperature of the first melt mixing section is 240℃ for 2 min, and the temperature of the second melt mixing section is 240℃ for 1 min. Nylon 6 is dried at 110℃ for 6 h before being added to the co-rotating twin-screw extruder, and MXD6 is dried at 110℃ for 8 h before being added to the co-rotating twin-screw extruder.

[0044] Example 4 This embodiment provides a nylon-polyolefin polymer alloy material and its preparation method, the preparation method specifically including the following steps: S1, 12-aminododecanoic acid, 1,12-dodecanediamine, and sodium hypophosphite are added to a reaction vessel. The mass ratio of 12-aminododecanoic acid to 1,12-dodecanediamine is 100:10, and the mass ratio of sodium hypophosphite to the total mass of 12-aminododecanoic acid and 1,12-dodecanediamine is 0.02:100. After purging with nitrogen, the mixture is heated to 185°C for pre-polymerization for 2.5 h, and then heated to 240°C for melt polymerization for 2.5 h to obtain amino-terminated nylon 12 oligomer. The number average molecular weight of the amino-terminated nylon 12 oligomer is 2500 g / mol, and the amino end group concentration is 760 mmol / kg. S2, caprolactam, 6-aminohexanoic acid, adipic acid, and sodium hypophosphite were added to a reaction vessel. The mass ratio of caprolactam, 6-aminohexanoic acid, and adipic acid was 90:10:3.5, and the mass ratio of sodium hypophosphite to the total mass of caprolactam, 6-aminohexanoic acid, and adipic acid was 0.03:100. After purging with nitrogen, the mixture was heated to 185°C for ring-opening polymerization for 3 hours, and then heated to 245°C for polycondensation for 2.5 hours to obtain carboxyl-terminated nylon 6 oligomers. The number average molecular weight of the carboxyl-terminated nylon 6 oligomers was 1900 g / mol, the carboxyl-terminated concentration was 640 mmol / kg, and the molar ratio of carboxyl-terminated concentration to amino-terminated concentration was 0.8:1. S3, amino-terminated nylon 12 oligomer and maleic anhydride-grafted polypropylene are added to a twin-screw extruder at a mass ratio of 20:80 and subjected to a first melt reaction at 225°C for 2 minutes to obtain long-chain nylon-polyolefin interface masterbatch; the maleic anhydride-grafted polypropylene has a melt flow rate of 5 g / 10 min at 230°C and 2.16 kg. S4, the carboxyl-terminated nylon 6 oligomer and the ethylene-acrylate-glycidyl methacrylate copolymer are added to a twin-screw extruder at a mass ratio of 10:90, and a second melt reaction is carried out at 240°C for 1 min to obtain nylon 6-polyolefin interface masterbatch; the mass content of glycidyl methacrylate structural units in the ethylene-acrylate-glycidyl methacrylate copolymer is 8 wt.%, and the molar ratio of epoxy groups to carboxyl-terminated nylon 6 oligomers is 0.6:1; S5, Nylon 6, Nylon 66, polypropylene, long-chain nylon-polyolefin interface masterbatch, nylon 6-polyolefin interface masterbatch, MXD6, hindered phenolic antioxidant, phosphite antioxidant, and ethylene bis-stearamide are added to the first feed port of a co-rotating twin-screw extruder and melt-mixed in the first melt mixing section to obtain the first melt; the mass ratio of nylon resin, polypropylene, long-chain nylon-polyolefin interface masterbatch, nylon 6-polyolefin interface masterbatch, antioxidant, ethylene bis-stearamide, and 2,2′-(1,4-phenylene)dioxazoline is 70:15:10:8:0.5:0.8:0.9, the mass ratio of nylon 6 to nylon 66 is 3:7, the mass ratio of hindered phenolic antioxidant to phosphite antioxidant is 2:1, and the mass ratio of MXD6 to nylon resin is 9:70; S6, 2,2′-(1,4-phenylene)dioxazoline is fed into a co-rotating twin-screw extruder through a side feed port located downstream of the first melt mixing section. It is then melt-mixed with the first melt in the second melt mixing section. After extrusion, cooling, and pelletizing, a nylon-polyolefin polymer alloy material is obtained. The co-rotating twin-screw extruder has an aspect ratio of 50, a screw speed of 500 r / min, a first melt mixing section temperature of 270℃ for 0.8 min, and a second melt mixing section temperature of 260℃ for 0.4 min. Nylon 6 and Nylon 66 are dried at 105℃ for 6 h before being added to the co-rotating twin-screw extruder, and MXD6 is dried at 100℃ for 10 h before being added to the co-rotating twin-screw extruder.

[0045] Comparative Example 1 This comparative example provides a nylon-polyolefin polymer alloy material and its preparation method. The difference between this and Example 1 is that long-chain nylon-polyolefin interface masterbatch and nylon 6-polyolefin interface masterbatch are not prepared. Instead, maleic anhydride-grafted ethylene-octene copolymer and ethylene-glycidyl methacrylate copolymer are directly added as reactive compatibilizers to nylon 6 and ethylene-octene copolymer for melt mixing. Other process parameters and operating conditions are exactly the same as in Example 1.

[0046] Comparative Example 2 This comparative example provides a nylon-polyolefin polymer alloy material and its preparation method. The difference between this and Example 1 is that nylon 6-polyolefin interface masterbatch is not prepared. Instead, long-chain nylon-polyolefin interface masterbatch is prepared and added. Ethylene-glycidyl methacrylate copolymer is directly added to nylon 6, ethylene-octene copolymer and long-chain nylon-polyolefin interface masterbatch for melt mixing. Other process parameters and operating conditions are exactly the same as in Example 1.

[0047] Comparative Example 3 This comparative example provides a nylon-polyolefin polymer alloy material and its preparation method. The difference between this and Example 1 is that long-chain nylon-polyolefin interface masterbatch is not prepared. Instead, nylon 6-polyolefin interface masterbatch is prepared and added. Maleic anhydride-grafted ethylene-octene copolymer is directly added to nylon 6, ethylene-octene copolymer and nylon 6-polyolefin interface masterbatch for melt mixing. Other process parameters and operating conditions are exactly the same as in Example 1.

[0048] Comparative Example 4 This comparative example provides a nylon-polyolefin polymer alloy material and its preparation method. The difference between this example and Example 1 is that 2,2′-(1,3-phenylene)dioxazoline is not added through the side feed port located downstream of the first melt mixing section, but is added together with nylon 6, ethylene-octene copolymer, long-chain nylon-polyolefin interface masterbatch and nylon 6-polyolefin interface masterbatch through the first feed port of a co-rotating twin-screw extruder. Other process parameters and operating conditions are exactly the same as in Example 1.

[0049] Test method: Notched impact strength retention test before and after damp heat cycling: Each group of materials was injection molded into simply supported beam notched impact specimens, with specimen dimensions of 80mm × 10mm × 4mm and notch type A. After molding, the specimens were placed in an environment of 23℃ and 50% relative humidity for 24 hours, and the notched impact strength was tested according to GB / T 1043.1, recorded as the notched impact strength before damp heat cycling. Another batch of specimens was subjected to damp heat cycling treatment under the following conditions: placed in a constant temperature and humidity chamber at 85℃ and 85% relative humidity for 24 hours, then transferred to an environment of -40℃ for 2 hours, and then placed in an environment of 23℃ and 50% relative humidity for 2 hours, constituting one cycle, for a total of 5 cycles. After the damp heat cycling was completed, the specimens were placed in an environment of 23℃ and 50% relative humidity for 24 hours, and the notched impact strength was tested again according to GB / T 1043.1, recorded as the notched impact strength after damp heat cycling. The notched impact strength retention rate after damp heat cycling is calculated using the following formula: Retention rate = Notched impact strength after damp heat cycling / Notched impact strength before damp heat cycling × 100%.

[0050] Warpage Deformation Test: Each group of materials was injection molded into flat specimens measuring 120mm × 120mm × 2mm. The gate was positioned in the center of one side of the flat plate, allowing the melt to flow along the length of the plate. After demolding, the specimens were placed in an environment of 23℃ and 50% relative humidity for 24 hours. During testing, the specimens were placed naturally on a horizontal marble platform without applying any external force to flatten them, allowing the specimens to contact the platform in their natural state. The maximum vertical distance between the warped portion of the specimen and the platform was measured using a height gauge or laser displacement meter and recorded as the warpage deformation in mm. Measurements were taken at each of the four corners and the midpoints of the four sides of each specimen, and the maximum value was recorded as the warpage deformation of that specimen.

[0051] Molding shrinkage difference test: Each group of materials was injection molded into a flat sample with dimensions of 120mm × 120mm × 2mm. The gate was positioned in the middle of one side of the flat sample, allowing the melt to flow along the length of the flat sample. The length of the mold cavity in the melt flow direction and the width perpendicular to the flow direction were recorded. After demolding, the samples were placed in an environment of 23℃ and 50% relative humidity for 24 hours. The length of the sample in the melt flow direction and the width perpendicular to the flow direction were measured using calipers or a video measuring instrument. The molding shrinkage rate in the melt flow direction was calculated as "difference between mold cavity length and sample length / mold cavity length × 100%", and the molding shrinkage rate in the perpendicular flow direction was calculated as "difference between mold cavity width and sample width / mold cavity width × 100%". The molding shrinkage difference is the absolute value of the difference between the molding shrinkage rate in the melt flow direction and the molding shrinkage rate in the perpendicular flow direction, expressed as a percentage (%).

[0052] Dimensional change rate test after water absorption: Each group of materials was injection molded into strip specimens with dimensions of 80mm × 10mm × 4mm. After demolding, the specimens were placed in an environment of 23℃ and 50% relative humidity for 24 hours, and the initial length of the specimen was measured and recorded as L0. Subsequently, the specimens were completely immersed in deionized water at 23℃ for 24 hours. After removal, the surface moisture of the specimens was wiped off with filter paper, and the length after water absorption was measured within 5 minutes and recorded as L1. The dimensional change rate after water absorption was calculated using the following formula: Dimensional change rate after water absorption = (L1 - L0) / L0 × 100%. At least 5 specimens were tested for each group of materials, and the average value was taken as the test result.

[0053] The test results are shown in Table 1.

[0054] Table 1. Test results of nylon-polyolefin polymer alloy materials in Examples 1-4 and Comparative Examples 1-4

[0055] As shown in Table 1, compared to Example 1, Comparative Example 1 exhibits the following characteristics after hygrothermal cycling: decreased notched impact strength retention, increased warpage, increased difference in molding shrinkage, and increased dimensional change rate after water absorption; Comparative Example 2 exhibits the same characteristics after hygrothermal cycling: decreased notched impact strength retention, increased warpage, increased difference in molding shrinkage, and increased dimensional change rate after water absorption; Comparative Example 3 exhibits the same characteristics after hygrothermal cycling: decreased notched impact strength retention, increased warpage, increased difference in molding shrinkage, and increased dimensional change rate after water absorption; and Comparative Example 4 exhibits the same characteristics after hygrothermal cycling: decreased notched impact strength retention, increased warpage, increased difference in molding shrinkage, and increased dimensional change rate after water absorption.

[0056] This is because Comparative Example 1 did not pre-prepare long-chain nylon-polyolefin interface masterbatch and nylon 6-polyolefin interface masterbatch, but instead directly added maleic anhydride-grafted ethylene-octene copolymer and ethylene-glycidyl methacrylate copolymer. During the melt blending process, the reaction sites were more randomly distributed, and the interface lacked pre-grafted nylon segments. After wet heat cycling, the interface bonding state was more easily decayed, thus reducing the impact performance retention rate and decreasing the dimensional stability.

[0057] Comparative Example 2 did not prepare nylon 6-polyolefin interface masterbatch. Although the long-chain nylon-polyolefin interface masterbatch was retained in the system, the interface region lacked nylon 6 grafted segments that were compatible with the nylon matrix. The number of carboxyl sites that could participate in the subsequent reaction was reduced, and the interfacial connection between the nylon phase and the polyolefin phase was insufficient, resulting in a decrease in the interface retention ability after hygrothermia.

[0058] Comparative Example 3 did not prepare a long-chain nylon-polyolefin interface masterbatch. Although the nylon 6-polyolefin interface masterbatch was retained in the system, the low water absorption long-chain nylon transition segment was missing between the polyolefin phase and the nylon phase. Under humid and hot conditions, the difference in the size response of the two phases was more likely to be concentrated in the interface region, resulting in an increase in the warping deformation, the difference in molding shrinkage, and the size change rate after water absorption.

[0059] In Comparative Example 4, the bisoxazoline compound was not added from the downstream feed port, but was added from the first feed port along with other components. Some of the bisoxazoline was consumed in advance by the carboxyl end group during the initial melting and mixing process, resulting in a decrease in the effective reaction ratio of the interface region and a weakening of the interfacial chain bridging effect. Therefore, its overall performance was lower than that of Example 1.

[0060] The above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.

Claims

1. A method for preparing a nylon-polyolefin polymer alloy material, characterized in that, The preparation method includes the following steps: S1, long-chain nylon chain-forming raw materials are subjected to polycondensation reaction with diamine end-group regulators to obtain amino-terminated long-chain nylon oligomers; S2, caprolactam, 6-aminohexanoic acid and dicarboxylic acid regulators are subjected to ring-opening polymerization and polycondensation reaction to obtain carboxyl-terminated nylon 6 oligomers; S3, the amino-terminated long-chain nylon oligomer is subjected to a first melt reaction with maleic anhydride-grafted polyolefin to obtain long-chain nylon-polyolefin interface masterbatch. S4, the carboxyl-terminated nylon 6 oligomer is subjected to a second melt reaction with an epoxy-containing polyolefin to obtain nylon 6-polyolefin interface masterbatch; S5, Nylon resin, polyolefin resin, the long-chain nylon-polyolefin interface masterbatch, the nylon 6-polyolefin interface masterbatch, antioxidant and lubricant are added to the first feed port of the twin-screw extruder and melt-mixed in the first melt mixing section to obtain the first melt; S6, a bisoxazoline compound is added to a twin-screw extruder through a side feed port located downstream of the first melt mixing section, and melt-mixed with the first melt in the second melt mixing section. After extrusion, cooling, and pelletizing, a nylon-polyolefin polymer alloy material is obtained. In S1, the long-chain nylon chain-forming raw material and the diamine end-group regulator are used in any of the following combinations: Combination 1, wherein the long-chain nylon chain-forming raw material is 12-aminododecanoic acid, and the diamine end-group regulator is 1,12-dodecanediamine, to obtain amino-terminated nylon 12 oligomer; Combination 2, wherein the long-chain nylon chain-forming raw materials are hexamethylenediamine and sebacic acid, and the diamine end-group regulator is hexamethylenediamine, to obtain amino-terminated nylon 610 oligomer; Combination 3, the long-chain nylon chain-forming raw materials are decanediamine and sebacic acid, and the diamine end-group regulator is decanediamine, to obtain amino-terminated nylon 1010 oligomer.

2. The method for preparing a nylon-polyolefin polymer alloy material according to claim 1, characterized in that, In S1, when the amino-terminated long-chain nylon oligomer is an amino-terminated nylon 12 oligomer, the mass ratio of 12-aminododecanoic acid to 1,12-dodecanediamine is 100:(2-10); when the amino-terminated long-chain nylon oligomer is an amino-terminated nylon 610 oligomer, the mass ratio of the total amount of hexamethylenediamine to sebacic acid is (59-66):100; when the amino-terminated long-chain nylon oligomer is an amino-terminated nylon 1010 oligomer, the mass ratio of the total amount of sebacic acid to sebacic acid is (88-98):

100. In S2, the mass ratio of caprolactam, 6-aminohexanoic acid and dicarboxylic acid regulator is (80-95):(5-20):(2-8), and the dicarboxylic acid regulator is one or both of adipic acid and sebacic acid.

3. The method for preparing a nylon-polyolefin polymer alloy material according to claim 1, characterized in that, The number average molecular weight of the amino-terminated long-chain nylon oligomer is 1900-2800 g / mol, and the amino end group concentration is 360-840 mmol / kg; the number average molecular weight of the carboxyl-terminated nylon 6 oligomer is 900-2300 g / mol, and the carboxyl end group concentration is 460-1180 mmol / kg, and the molar ratio of the carboxyl end group concentration to the amino end group concentration is (0.8-1.4):

1.

4. The method for preparing a nylon-polyolefin polymer alloy material according to claim 1, characterized in that, In S1, the polycondensation reaction includes pre-polycondensation and melt polycondensation. The pre-polycondensation temperature is 180-200℃ and the time is 1.5-3h; the melt polycondensation temperature is 220-245℃ and the time is 2-4h. In S2, the ring-opening polymerization is carried out at a temperature of 180-200℃ for 2-4 hours; the polycondensation reaction is carried out at a temperature of 230-250℃ for 2-4 hours. S1 and S2 are carried out under a nitrogen atmosphere, and sodium hypophosphite is added to S1 and S2. The mass ratio of sodium hypophosphite to the total mass of the reaction raw materials is (0.01-0.1):

100.

5. The method for preparing a nylon-polyolefin polymer alloy material according to claim 1, characterized in that, In S3, the mass ratio of the amino-terminated long-chain nylon oligomer to the maleic anhydride-grafted polyolefin is (5-25):(75-95), the temperature of the first melting reaction is 190-230℃, and the reaction time is 1-5 min. In S4, the mass ratio of the carboxyl-terminated nylon 6 oligomer to the epoxy-containing polyolefin is (5-30):(70-95), the temperature of the second melting reaction is 200-240℃, and the reaction time is 1-5 min; The molar ratio of the epoxy group in the epoxy-containing polyolefin to the carboxyl end group in the carboxyl-terminated nylon 6 oligomer is (0.2-0.8):

1.

6. The method for preparing a nylon-polyolefin polymer alloy material according to claim 1, characterized in that, The maleic anhydride-grafted polyolefin is one or both of maleic anhydride-grafted ethylene-octene copolymer and maleic anhydride-grafted polypropylene; the melt flow rate of the maleic anhydride-grafted ethylene-octene copolymer at 190℃ and 2.16kg is 0.5-10g / 10min, and the melt flow rate of the maleic anhydride-grafted polypropylene at 230℃ and 2.16kg is 5-50g / 10min. The epoxy-containing polyolefin is one or both of ethylene-glycidyl methacrylate copolymer and ethylene-acrylate-glycidyl methacrylate copolymer, and the mass content of glycidyl methacrylate structural units in the epoxy-containing polyolefin is 2-10 wt.%.

7. The method for preparing a nylon-polyolefin polymer alloy material according to claim 1, characterized in that, In S5 and S6, the mass ratio of the nylon resin, polyolefin resin, long-chain nylon-polyolefin interface masterbatch, nylon 6-polyolefin interface masterbatch, antioxidant, lubricant, and bisoxazoline compound is (50-75):(10-30):(3-12):(3-12):(0.2-1.5):(0.2-1.5):(0.2-1.2). The nylon resin is one or both of nylon 6 and nylon 66; the polyolefin resin is one or both of polypropylene and ethylene-octene copolymer; the bisoxazoline compound is one or both of 2,2′-(1,3-phenylene)dioxazoline and 2,2′-(1,4-phenylene)dioxazoline.

8. The method for preparing a nylon-polyolefin polymer alloy material according to claim 1, characterized in that, In S5, MXD6 is also added, and the mass ratio of MXD6 to nylon resin is (3-12):(50-75). The antioxidant is one or two of hindered phenolic antioxidants and phosphite antioxidants; the lubricant is one or more of ethylene bis-stearamide, pentaerythritol stearate, and calcium stearate. The twin-screw extruder is a co-rotating twin-screw extruder with a length-to-diameter ratio of 44-52 and a screw speed of 250-500 r / min; the temperature of the first melt mixing section is 240-275℃, and the temperature of the second melt mixing section is 240-270℃; the nylon resin and MXD6 are dried before being added to the twin-screw extruder, and the drying temperature is 100-120℃ for 6-10 hours.

9. A nylon-polyolefin polymer alloy material, characterized in that, It is prepared by the preparation method according to any one of claims 1-8.

Citation Information

Patent Citations

  • Nylon toughener, and preparation method and application thereof

    CN105693890A

  • Toughened nylon, nylon toughening agent and preparation method

    CN106496610A